EVALUASI PROGRAM PEMBELAJARAN TEMATIK BAGI SISWA KELAS 5 SEKOLAH DASAR - Nisrina Ajrina Nur Hidayah; Siti Fatimah (Elementary School and Education Journal, 2025)
Evaluasi Pembelajaran Tematik Bagi Siswa Kelas 5 Sekolah Dasar, this study aims to identify: (1) planning a thematic learning program for grade V elementary school students on the science subject theme 6 titled heat and its displacement. The type of research employed was evaluation research using the countenance stake model. The population in this research included eight public schools in Kedungbanteng District, Banyumas. The sample of this research was divided using cluster random sampling which was divided into two regions, namely the northern region (Elementary School of 1 Kutaliman, Elementary School of 2 Kutaliman) and the southern region (Elementary School of 1 Beji, Elementary School of 2 Beji). The sampling of teachers used purposive sampling. The stake model divides the research into three stages, namely antecedent, transaction, and outcome. Antecedent components included curriculum sub-components, students' initial abilities, learning facilities, teacher linearity, and teacher understanding of science learning. The results show that: (1) the overall mean of the Antecedent component is 82 from the ideal value of 100, indicating a very good category.